Rancang Bangun Aplikasi Pemesanan Tiket Kereta Cepat Jakarta – Bandung Khusus Lansia Dan Ibu Hamil Berbasis Mobile Web Secara Online - Mahesa, Oki Kus (ITB Ahmad Dahlan Jakarta, 2021)
PT. Indonesia Indonesia Fast Train (KCIC) has begun to build its Project, namely the Jakarta-Bandung Fast Train, look at the application features of PT. KAI access that does not yet have a need for the elderly and pregnant wome to get special service, then in this study the train ticket booking application was designed Fast Jakarta-Bandung Special for the Elderly and Pregnant Women Online-Based Android Web. Ticket booking application This mobile web-based fast train aims to help the elderly and pregnant women make it easier in booking fast train tickets effectively and efficiently because the feature can be used in a reltime, inside in order to improve services aimed at making it easier for the Elderly and Pregnant Women to do Fast train ticket reservations, this application makes the elderly and pregnant women do not need to queue at the time will check in to get into the fast train. This research methodology uses Disciplined methodology Agile Delivery System design phase aims as a preparation for system design, sketching how the system is formed and provide a clear picture of the development to build the system The design of this system using the DAD (Disciplined Agile Delivery) DAD (Ambler and Lines) methodology, 2012). The results of this study are based on innovations of features that make it easy for the elderly and pregnant women to be designed then developed so as to produce a Jakarta-Bandung Cepata train ticket booking application specifically for the elderly and online android-based pregnant women who will help and facilitate the elderly and pregnant women in ordering fast train tickets, fast train ticket transactions and the use of fast trains jakarta-bandung.